A citizen science approach toward parents-administered remote language assessment for bilingual Mandarin-English children: an evaluation of in-person and telehealth settings - Du, Yao; Tang, Yueyan; Fong, Ka Kei; Liu, Yusa; Wang, Danyang; Tu-Shea, Xintian; Liu, Yilan; Zheng, Qingxiao; Quan, Shuang; Xiong, Jinjun; Sheng, Li (Frontiers in Education, 2026)
IntroductionThe growing population of bilingual children and lack of bilingual clinicians have created an increased need for reliable and accessible bilingual language assessment to accurately detect language delays and disorders globally. To address this growing need, this study evaluated the Mandarin-English Receptive Language Screener (MERLS), a web-based receptive language assessment designed for bilingual Mandarin-English (ME) speaking children.MethodsUsing a citizen science approach, bilingual ME speaking parents based in the United States served as the test administrators. This two-phase study compared bilingual ME speaking children’s performance and parent-child interactions across in-person (n = 16) and telehealth (n = 43) settings. Participants in both phases were typically developing children aged 3–10 years who used Mandarin and English for at least 20% of their daily communication.ResultsIn Phase I (in-person), despite variability in parent behaviors during administration, parent-administered assessments demonstrated comparable test-retest reliability (Pearson correlation: r = 0.95, p < 0.01) and item-by-item agreement (82%) to researcher-administered assessments. These reliability metrics are comparable to those of established standardized child language assessments (e.g., PPVT-5 and the QUILS). In Phase II (telehealth), platform improvements (e.g., educational quizzes and videos on proper test administration) significantly reduced interfering parent behaviors (Mandarin items: W = 485, p = 0.004; English items: W = 482, p = 0.003) without affecting children’s test performance.DiscussionThese results support the feasibility of using a citizen science approach and a digital assessment platform MERLS for parent-administered language assessments. Such innovative assessment approach has great potentials to increase access to accurate and reliable language assessment services for bilingual ME speaking children in the United States. The findings offer clinical and technical insights for developing bilingual child language assessments across both in-person and telehealth settings.